Nudging Green Preferences: Evidence from a Laboratory Experiment - Permana, Yudistira Hendra (World Scientific, 2022)
Environmental degradation has been one of the major global concerns in the last few decades. Efforts are made to improve our environment including how to alter consumers' preferences toward the use of environmental-friendly products. We conduct an online laboratory experiment to investigate the effectiveness of information and nudges regarding green products using social (cultural) identity-specific campaigns. Our study shows that information and green nudges are unable to alter subjects' risk aversion and time preference. However, green nudges are effective to motivate subjects to allocate more to green product and that differs the effectiveness between information and green nudges in our context. Lastly, we find that some green perceptions are associated with subjects' willingness to pay for green products and characteristics. We conclude with a discussion of how to effectively deliver nudges in promoting green consumption.